Relationship between state justice and arbitral justice : Comparative study France-OHADA - (:unkn) unknown (My University, 2019)
Arbitration has been used to resolving cases appreciated by international trade actors. However, well-functioning depends upon state justice. Both devices should have maintain a fusional and competitive relationship. The unfolding of this relationship can reciprocally bring complications and mistrust. State judge is referee’s collaborator despite the spacing of reports in France and several other states in sub-Saharan Africa. These states recognize the explicit and implicit power of state justice during arbitration. This study approaches courts assigned to the arbitrator and judge during their challenge. In order to accentuate and sustain the smooth running of arbitration in France and Francophone Africa, this research has been focused on the issue of economic development. After listing realities hindering the flowering of arbitration in this part of Africa, some solutions have been proposed to preserve this method of dispute resolution of dysfunction.
Keywords: African Research